Leadership Ethos: Addressing Leadership Dilemma in the 21st Century Business Environment. (4th March 2023) - Ndalamba, Ken Kalala; Ndalamba, Neusa Joaquim; Caldwell, Cam
Abstract: The purpose of this study is to examine the significance of vision, virtues and values—attributes of leadership ethos in shaping a framework to fulfill ethical duties owed by leaders. The paper begins by highlighting examples of some types of modern leadership associated with selected macro environment forces namely political, religious and cultural. It then identifies leadership ethos as a leadership perspective that can guide leaders toward fulfilling their ethical duties through vision, virtues and values as premises of trust. The study discusses compliance-based and integrity-based leadership as indication of the level of trust followers have in their leaders based on the nature of ethical duties owed by leaders. Following are four action steps for the implementation and practice of leadership ethos with a view of enhancing the fulfilment of ethical duties owed by the leaders. By incorporating the three key elements of LE (vision, virtues and values), leaders should inspire others to transcend their own self-interests in the pursuit of a higher purpose, pursue organizational excellence while honouring duties to employees/followers to keep them informed, provide them with the resources to achieve individual goals, and seek their highest potential.